Improving Service Quality in the Banyuwangi Regency Government through Community Satisfaction Index - Mukhrojin, Moh; Hidyantari, Erlyna; Hardiono, Hardiono (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
The measure of the success of service delivery is determined by the level of satisfaction of service recipients. Satisfaction of service recipients is achieved if service recipients receive services in accordance with what is needed and expected. This research aims to measure excellent service quality based on the perspective of community participation through a community satisfaction index survey stipulated in the Decree of the Minister of Administrative Reform No. 14 of 2017 concerning Guidelines for Preparing IKM for Government Agency Service Units. The survey used a purposive survey method approach, taking 165 respondents who received sub-district office services in Banyuwangi Regency. Inferential analysis of community satisfaction survey data is used to measure the community satisfaction index and service quality from the perspective of the community receiving services. The results of this research show a value of 93.16 which explains that the public can feel very satisfied with the services of the sub-district office, while the IPA measurement obtained a value of 3.73, which means that employees at the sub-district office are able to provide excellent service and provide excellent service in the community service process. The results of this survey can be concluded that measuring the community satisfaction index is relevant and more effective for assessing the quality of services provided by local government officials.